Lithium battery positive plate as well as preparation method and application thereof
By adopting a multi-layer structure on the positive electrode of lithium battery, combined with the blending of lithium manganese iron phosphate, polycrystalline ternary materials and lithium manganese oxide, the shortcomings of lithium-ion batteries in terms of safety performance, circulation performance and low-temperature performance are solved, and the improvement is achieved High energy density and longer battery life.
Patent Information
- Application Number
- CN202411257161.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-09
AI Technical Summary
The existing lithium-ion battery positive electrode materials have shortcomings in terms of safety performance, circulation performance and low-temperature performance. In particular, the spinel structure and olivine structure of lithium manganese iron phosphate material lead to uneven diffusion of lithium ions, affecting the safety and performance of the battery.
The lithium battery positive electrode sheet adopts a multi-layer structure, including a lithium manganese iron phosphate layer sequentially coated from the current collector surface, a polycrystalline ternary material blended with lithium manganese iron phosphate layer and lithium manganese oxide layer, using polycrystalline ternary material and nanophosphate The blending of lithium manganese manganese optimizes current and interface impedance, and improves battery safety and cycling performance.
It significantly improves the safety performance, circulation performance and energy density of lithium batteries, while improving low-temperature performance and extending the battery life and range.
Smart Images

Figure BDA0005034439790000161
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a lithium battery positive electrode sheet and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] With the continuous development of the electric vehicle market, higher requirements are placed on the energy density and cycle performance of lithium-ion batteries in order to obtain longer service life and mileage. As a new energy storage device, high energy density and long cycle life lithium-ion batteries have become the performance that consumers are urgently concerned about. As an important component of lithium-ion batteries, positive and negative electrode materials are directly related to the capacity, voltage platform and energy density of lithium-ion batteries. The inconsistency of the diffusion rate of the electrode ions seriously affects the performance of the battery, which has attracted great attention from researchers.
[0004] The current mainstream positive electrode materials include lithium iron phosphate positive electrode, ternary positive electrode, lithium iron manganese phosphate positive electrode, etc. Although lithium iron phosphate positive electrode materials have stable structure and good safety performance, they have low gram capacity and poor low temperature performance; ternary positive electrode materials have high reversible capacity, but their safety performance needs to be improved; and lithium iron manganese phosphate has poor processing performance and is not suitable for single use. When lithium iron manganese phosphate is directly mixed with other positive electrode materials, there are still some defects: lithium manganese oxide with spinel structure is a three-dimensional structure, while lithium iron manganese phosphate with olivine structure is a one-dimensional structure, which makes the lithium ion diffusion rate on lithium manganese oxide with spinel structure better than lithium iron manganese phosphate, resulting in different lithium deintercalation speeds, battery safety and performance cannot be guaranteed, and the different ion diffusion rates of the battery cells lead to battery performance degradation.
[0005] Therefore, there is an urgent need to develop a positive electrode material and a preparation method thereof that can meet the safety performance and electrochemical performance of the battery cell, have excellent low-temperature performance and cycle performance, and meet the production and processing performance. Summary of the invention
[0006] In order to solve the deficiencies of the prior art, the purpose of the present invention is to provide a lithium battery positive electrode plate and a preparation method and application thereof. The lithium battery positive electrode plate provided by the present invention can improve the battery safety performance, rate performance, and battery cycle performance.
[0007] In order to achieve the above object, the technical solution of the present invention is:
[0008] A first aspect of the present invention provides a lithium battery positive electrode sheet, comprising a current collector and a positive electrode multilayer structure attached to the current collector;
[0009] The positive electrode multilayer structure is composed of a lithium iron manganese phosphate layer, a polycrystalline ternary material mixed lithium iron manganese phosphate layer and a lithium manganate layer from top to bottom, and the lithium manganate layer is attached to the surface of the current collector;
[0010] The polycrystalline ternary material is lithium nickel cobalt manganese oxide.
[0011] The second aspect of the present invention provides a method for preparing the above-mentioned lithium battery positive electrode sheet, comprising the following steps:
[0012] Prepare lithium iron manganese phosphate slurry; prepare polycrystalline ternary material mixed with lithium iron manganese phosphate slurry; prepare lithium manganate slurry;
[0013] Lithium iron manganese phosphate slurry, polycrystalline ternary material mixed with lithium iron manganese phosphate slurry and lithium manganate slurry are sequentially coated on the surface of the current collector, and then dried, rolled and die-cut to obtain a lithium battery positive electrode sheet.
[0014] According to a third aspect of the present invention, a lithium battery is provided, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; the positive electrode sheet is the above-mentioned lithium battery positive electrode sheet or a lithium battery positive electrode sheet prepared by the above-mentioned preparation method.
[0015] The beneficial effects of the present invention are:
[0016] The present invention obtains a lithium battery positive electrode sheet by optimizing the positive electrode multilayer structure attached to the current collector. The direction close to the current collector is the lower layer, and the direction away from the current collector is the upper layer. The positive electrode multilayer structure attached to the current collector is sequentially arranged from bottom to top as a lithium manganate layer, a polycrystalline ternary material mixed lithium iron manganese phosphate layer, and a lithium iron manganese phosphate layer. Since the current in the upper material area is large, the upper layer is lithium iron manganese phosphate material, which can accelerate the diffusion of lithium ions in lithium iron manganese phosphate and improve the safety performance of the battery; the polycrystalline ternary positive electrode active material and nano lithium iron manganese phosphate are mixed as the middle layer. Since the nano lithium iron manganese phosphate has a small particle size and an olivine structure, the excellent safety and cycle performance of the lithium iron manganese phosphate positive electrode material are used to improve the cycle, rate and safety performance of the polycrystalline ternary positive electrode active material. The upper layer is nano-scale lithium iron manganese phosphate material, and the middle layer is a mixture of polycrystalline ternary and nano-scale lithium iron manganese phosphate, which can improve compaction and improve its interface impedance, thereby further improving its cycle performance while improving safety; since lithium manganate has better conductivity than polycrystalline ternary material, the lower layer is lithium manganate positive electrode material. In addition, since the spinel lithium manganate material has poor high temperature performance, being arranged in the lower layer also reduces more direct contact with the electrolyte, reduces the occurrence of side reactions, and is beneficial to the long cycle of the battery. Therefore, the use of a multi-layer structure plays a significant role in improving safety performance and battery cycle performance. At the same time, the middle layer is a polycrystalline ternary material mixed with lithium manganese iron phosphate material, which can improve the safety performance of the battery while also taking into account the energy density of the battery cell. DETAILED DESCRIPTION
[0017] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] A first typical embodiment of the present invention provides a lithium battery positive electrode sheet, including a current collector and a positive electrode multilayer structure attached to the current collector;
[0019] The positive electrode multilayer structure is composed of a lithium iron manganese phosphate layer, a polycrystalline ternary material mixed lithium iron manganese phosphate layer and a lithium manganate layer from top to bottom, and the lithium manganate layer is attached to the surface of the current collector;
[0020] The polycrystalline ternary material is lithium nickel cobalt manganese oxide.
[0021] It should be noted that the thickness of the positive electrode multilayer structure is determined based on the cell capacity and energy density, and should not be too thick or too thin. The total thickness of the positive electrode multilayer structure and the current collector is generally between 80 mm and 200 mm.
[0022] Since the current in the upper material area is large, the upper layer is lithium iron manganese phosphate material, which can accelerate the diffusion of lithium ions in lithium iron manganese phosphate and improve the safety performance of the battery; the polycrystalline ternary positive electrode active material and nano lithium iron manganese phosphate are mixed as the middle layer. Since the lithium iron manganese phosphate has a small particle size and an olivine structure, the excellent safety and cycle performance of the lithium iron manganese phosphate positive electrode material are used to improve the cycle, rate and safety performance of the polycrystalline ternary positive electrode active material. The upper layer is lithium iron manganese phosphate material, and the middle layer is a mixture of polycrystalline ternary and lithium iron manganese phosphate, which can improve compaction and improve its interface impedance, thereby further improving its cycle performance while improving safety; since lithium manganate has better conductivity than polycrystalline ternary material, the lower layer is lithium manganate positive electrode material. In addition, since the spinel lithium manganate material has poor high temperature performance, being arranged in the lower layer also reduces more direct contact with the electrolyte, reduces the occurrence of side reactions, and is beneficial to the long cycle of the battery. Therefore, the use of a multi-layer structure plays a significant role in improving safety performance and battery cycle performance. At the same time, the middle layer is a polycrystalline ternary material mixed with lithium manganese iron phosphate material, which can improve the safety performance of the battery while also taking into account the energy density of the battery cell.
[0023] In some examples of this embodiment, the current collector includes but is not limited to aluminum foil, copper foil and titanium mesh. Since aluminum foil has the advantages of high strength, good conductivity, easy surface treatment and low cost, the current collector is preferably aluminum foil.
[0024] In some examples of this embodiment, the median particle size D50 of the lithium manganese iron phosphate is preferably 200-1500 nm, more preferably 500-1200 nm, and more preferably 800-1000 nm.
[0025] In some examples of this embodiment, the median particle size D50 of the polycrystalline ternary material is preferably 6-12 μm, more preferably 8-10 μm.
[0026] In some examples of this embodiment, the median particle size D50 of the lithium manganate is preferably 8-15 μm, more preferably 10-13 μm.
[0027] The present invention adopts nano-scale lithium iron manganese phosphate material, which is doped with micron-scale polycrystalline ternary material on the one hand, which can improve compaction and improve its interface impedance, and further improve the cycle performance of lithium batteries while improving safety. The large and small particles of the intermediate layer positive electrode active material are compounded, and the polycrystalline ternary positive electrode active material is compounded with nano-lithium iron manganese phosphate. The nano-lithium iron manganese phosphate particles are relatively fine and can be filled in the gaps between the polycrystalline ternary positive electrode active material and the lithium manganate positive electrode material, thereby improving the compaction density of the composite material and the contact between the particles, and reducing the internal resistance of the pole piece. The multi-layer structure of the active material improves the battery's rate charging and rate discharging capabilities, and the olivine structure lithium iron manganese phosphate material improves the battery's safety performance.
[0028] In some examples of this embodiment, the chemical formula of the lithium nickel cobalt manganese oxide is LiNi x Co y Mn 1-x-y O2, where 0<x<1, 0<y<1, x+y<1.
[0029] In some examples of this embodiment, the lithium manganese iron phosphate has an orthorhombic olivine crystal structure and a chemical formula of LiMn x Fe 1-x PO4, wherein 0.5≤x<1.0, preferably, 0.6≤x≤0.8.
[0030] Lithium manganese iron phosphate with olivine crystal structure gives it high stability and good safety. The characteristic of olivine lithium manganese iron phosphate is that even if all lithium ions are released during charging, the structure will not collapse, thus ensuring the safety performance of the battery. In addition, the crystal structure of lithium manganese iron phosphate gives it the potential advantage of high energy density, which is its biggest advantage over lithium iron phosphate.
[0031] In some examples of this embodiment, the lithium manganese oxide has a spinel structure, and its chemical formula is LiMn2O4.
[0032] In some examples of this implementation manner, in the polycrystalline ternary material-mixed nano-manganese iron lithium phosphate layer, the mass ratio of the polycrystalline ternary material to the nano-manganese iron lithium phosphate is preferably 50:50-99:2, and more preferably 70:30-80:20.
[0033] In some examples of this embodiment, the coating weight ratio of the lithium manganese iron phosphate layer, the polycrystalline ternary material mixed nano lithium manganese iron phosphate layer and the lithium manganate layer is preferably (1-10):(1-10):1, and more preferably (1-7):(2-8):1.
[0034] A second typical embodiment of the present invention provides a method for preparing the above-mentioned lithium battery positive electrode sheet, comprising the following steps:
[0035] Prepare lithium iron manganese phosphate slurry; prepare polycrystalline ternary material mixed with lithium iron manganese phosphate slurry; prepare lithium manganate slurry;
[0036] Lithium iron manganese phosphate slurry, polycrystalline ternary material mixed with lithium iron manganese phosphate slurry and lithium manganate slurry are sequentially coated on the surface of the current collector, and then dried, rolled and die-cut to obtain a lithium battery positive electrode sheet.
[0037] In some examples of this embodiment, the coating is: applying multiple layers of the slurry by extrusion coating.
[0038] A third typical embodiment of the present invention provides a lithium battery, which includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; the positive electrode sheet is the above-mentioned lithium battery positive electrode sheet or a lithium battery positive electrode sheet prepared by the above-mentioned preparation method.
[0039] In some examples of this embodiment, the negative electrode sheet is a negative electrode active composite material, including one or more of a graphite negative electrode material, a silicon oxide negative electrode material, and a modified silicon oxide negative electrode material. The negative electrode sheet is an existing product, for example, it can be prepared by referring to a preparation method of a negative electrode material for a lithium battery disclosed in patent CN117105231A.
[0040] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0041] In the following examples, the modified silicon-oxygen negative electrode is prepared by a method for preparing a negative electrode material for a lithium battery disclosed in patent CN117105231A. The specific preparation method is as follows: 100g of silicon-oxygen compound SiO x The particles were placed in a 1000 mL mixture of hydrogen peroxide and sulfuric acid (the mass concentration of sulfuric acid was 10%, and the mass concentration of hydrogen peroxide was 15%) for full reaction to obtain SiO containing hydroxyl groups. xparticles, wherein the mass ratio of hydrogen peroxide to sulfuric acid is 2:1; the treated SiO x There are a large number of hydroxyl groups attached to the surface of the particles, which x The particles were added to 100 g of titanium tert-butylate C 16 H 36 O4Ti ethanol solution (wherein the mass concentration of tert-butoxide titanium is 10%), so that it is chemically bonded to tert-butoxide titanium C 16 H 36 The O4Ti was connected more closely, stirred evenly, filtered, vacuum dried, and calcined at 600℃ for 4h in a tube furnace filled with inert gas to obtain TiO2 / SiO x Particles.
[0042] 100g of the prepared TiO2 / SiO x The particles were ultrasonically dispersed in deionized water, and hydrochloric acid (the mass concentration of hydrochloric acid was 10%) was added for acid adjustment for 1 hour to a pH value of about 3, and then 20 g of 3-aminopropyltrimethoxysilane was added dropwise to the acid solution through a peristaltic pump for reaction. After the addition, the reaction lasted for 12 hours, and the TiO2 / SiO2 containing amino groups was washed and dried by centrifugation with water and ethanol to obtain x Particles, that is: modified silicon-oxygen negative electrode.
[0043] In the following examples, the preparation method of the carboxyl-containing binder CMC is as follows: at room temperature, vinyl carbonate is added to a polymerization system of styrene and butadiene (styrene and butadiene are mixed in a mass ratio of 1:1) to react, and the amount of vinyl carbonate added is 50% of the mass of the polymerization system of styrene and butadiene. After the reaction is completed, the concentration is diluted to 3%, and the pH is adjusted to neutral to obtain a carboxyl-containing binder.
[0044] Example 1
[0045] A method for preparing a lithium ion battery comprises the following steps:
[0046] (a) Preparation of positive electrode for lithium-ion batteries
[0047] Prepare the lower layer spinel lithium manganate slurry ①, the concentration of which is 60wt%, D 50 13±1μm;
[0048] The middle layer polycrystalline ternary positive electrode material and nano manganese iron phosphate lithium positive electrode material are compounded in a mass ratio of 70:30 to prepare a mixed slurry②. The chemical formula of the ternary positive electrode material is: LiNi 0.8 Co 0.1 Mn0 .1 O2, particle size: 8-12 μm; nano-manganese iron lithium phosphate particle size D 501±0.5μm, solvent type: NMP, dosage: 45% of the total slurry;
[0049] Prepare the upper layer of lithium manganese iron phosphate slurry ③, the concentration of which is 50wt%, the solvent is NMP, and the particle size is: D 50 1±0.5μm.
[0050] The three types of positive electrode slurries were coated in multiple layers by extrusion coating, in which the coating weight ratio of the lower layer, the middle layer and the upper layer was 1:5:4. The positive electrode sheets were obtained after drying, rolling and die-cutting.
[0051] (b) Preparation of lithium-ion battery negative electrode
[0052] The graphite negative electrode and the modified silicon oxide negative electrode were compounded in a mass ratio of 95:5 as a negative electrode composite active material, the negative electrode composite active material was mixed with carbon black Super-P, a carboxyl-containing binder CMC and SBR in a mass ratio of 96:1:1.3:1.7, added into solvent pure water and fully dissolved and stirred to obtain a negative electrode slurry, the negative electrode slurry was coated on a 6 μm thick copper foil, and the negative electrode sheet was obtained after drying, rolling and cutting.
[0053] (c) Preparation of lithium-ion batteries
[0054] The positive and negative electrode sheets prepared in (a) and (b) are assembled together with the separator, packaged and injected with electrolyte, and then the required lithium-ion batteries are obtained by chemical composition and charge and discharge tests are performed.
[0055] Example 2
[0056] A method for preparing a lithium ion battery comprises the following steps:
[0057] (a) Preparation of positive electrode for lithium-ion batteries
[0058] A lower layer spinel lithium manganate slurry ① was prepared, which had the same particle size, slurry solvent and concentration as those in Example 1.
[0059] The intermediate layer polycrystalline ternary positive electrode material and the nano-manganese iron phosphate lithium positive electrode material are compounded in a mass ratio of 80:20 to prepare a mixed slurry ②. Except for the above ratio, the other parameters (particle size, slurry solvent and concentration) are the same as those in Example 1.
[0060] The upper layer of lithium manganese iron phosphate slurry ③ has the same particle size, slurry solvent and concentration as those in Example 1.
[0061] The three types of positive electrode slurries were coated in multiple layers by extrusion coating, in which the coating weight ratio of the lower layer, the middle layer and the upper layer was 2:5:3. The positive electrode sheets were obtained after drying, rolling and die-cutting.
[0062] (b) Preparation of lithium-ion battery negative electrode
[0063] The graphite negative electrode and the modified silicon oxide negative electrode were compounded in a mass ratio of 95:5 as a negative electrode composite active material, the negative electrode composite active material was mixed with carbon black Super-P, a carboxyl-containing binder CMC and SBR in a mass ratio of 96:1:1.3:1.7, added into solvent pure water and fully dissolved and stirred to obtain a negative electrode slurry, the negative electrode slurry was coated on a 6 μm thick copper foil, and the negative electrode sheet was obtained after drying, rolling and cutting.
[0064] (c) Preparation of lithium-ion batteries
[0065] The positive and negative electrode sheets prepared in (a) and (b) are assembled together with the separator, packaged and injected with electrolyte, and then the required lithium-ion batteries are obtained by chemical composition and charge and discharge tests are performed.
[0066] Example 3
[0067] A method for preparing a lithium ion battery comprises the following steps:
[0068] (a) Preparation of positive electrode for lithium-ion batteries
[0069] A lower layer spinel lithium manganate slurry ① was prepared, which had the same particle size, slurry solvent and concentration as those in Example 1.
[0070] The intermediate layer polycrystalline ternary positive electrode material and the nano-manganese iron phosphate lithium positive electrode material are compounded in a mass ratio of 70:30 to prepare a mixed slurry ②. Except for the above ratio, the other parameters (particle size, slurry solvent and concentration) are the same as those in Example 1.
[0071] The upper layer of lithium manganese iron phosphate slurry ③ has the same particle size, slurry solvent and concentration as those in Example 1.
[0072] The three types of positive electrode slurries were coated in multiple layers by extrusion coating, in which the coating weight ratio of the lower layer, the middle layer and the upper layer was 1:7:2. The positive electrode sheets were obtained after drying, rolling and die-cutting.
[0073] (b) Preparation of lithium-ion battery negative electrode
[0074] The graphite negative electrode and the modified silicon oxide negative electrode were compounded in a mass ratio of 95:5 as a negative electrode composite active material, the negative electrode composite active material was mixed with carbon black Super-P, a carboxyl-containing binder CMC and SBR in a mass ratio of 96:1:1.3:1.7, added into solvent pure water and fully dissolved and stirred to obtain a negative electrode slurry, the negative electrode slurry was coated on a 6μm copper foil, and the negative electrode sheet was obtained after drying, rolling and cutting.
[0075] (c) Preparation of lithium-ion batteries
[0076] The positive and negative electrode sheets prepared in (a) and (b) are assembled together with the separator, packaged and injected with electrolyte, and then the required lithium-ion batteries are obtained by chemical composition and charge and discharge tests are performed.
[0077] Comparative Example 1
[0078] A method for preparing a lithium ion battery comprises the following steps:
[0079] (a) Preparation of positive electrode for lithium-ion batteries
[0080] The polycrystalline ternary material, lithium iron manganese phosphate material and lithium manganese oxide positive electrode material are mixed in a ratio of 5:3:2 to form a positive electrode composite active material. Among them, the chemical formula of the polycrystalline ternary material is LiNi 0.8 Co 0.1 Mn0 .1 O2, particle size: D 50 : 8~12μm; LiMnFePO4 particle size: D 50 :1±0.5μm; LiMnO3 particle size: D 50 : 13±1μm. The positive electrode composite active material, conductive agent Super-P, carbon nanotube CNT slurry, and binder PVDF were mixed in a mass ratio of 96.5:1:0.5:2, added to the solvent NMP through a multi-step method, and fully stirred to obtain a positive electrode mixed slurry, and then the positive electrode mixed slurry was coated on a 12μm thick aluminum foil, and the positive electrode sheet was obtained after drying, rolling, and die cutting.
[0081] (b) Preparation of lithium-ion battery negative electrode
[0082] The graphite negative electrode and the modified silicon oxide negative electrode were compounded in a mass ratio of 95:5 as a negative electrode composite active material, the negative electrode composite active material was mixed with carbon black Super-P, a carboxyl-containing binder CMC and SBR in a mass ratio of 96:1:1.3:1.7, added into solvent pure water and fully dissolved and stirred to obtain a negative electrode slurry, the negative electrode slurry was coated on a 6 μm thick copper foil, and the negative electrode sheet was obtained after drying, rolling and cutting.
[0083] (c) Preparation of lithium-ion batteries
[0084] The positive and negative electrode sheets prepared in (a) and (b) are assembled together with the separator, packaged and injected with electrolyte, and then the required lithium-ion batteries are obtained by chemical composition and charge and discharge tests are performed.
[0085] Comparative Example 2
[0086] A method for preparing a lithium ion battery comprises the following steps:
[0087] (a) Preparation of positive electrode for lithium-ion batteries
[0088] The ternary material and the lithium iron manganese phosphate positive electrode material are mixed in a ratio of 5:5 to form a positive electrode composite active material (the ternary material and the lithium iron manganese phosphate material are consistent with those in Comparative Example 1), the positive electrode composite active material, the conductive agent Super-P, the carbon nanotube CNT slurry, and the binder PVDF are mixed in a mass ratio of 96.5:1:0.5:2, added to the solvent NMP through a multi-step method, and fully stirred to obtain a positive electrode mixed slurry, and then the positive electrode mixed slurry is coated on a 12μm thick aluminum foil, and the positive electrode sheet is obtained after drying, rolling, and die-cutting.
[0089] (b) Preparation of lithium-ion battery negative electrode
[0090] The graphite negative electrode and the modified silicon oxide negative electrode were compounded in a mass ratio of 95:5 as a negative electrode composite active material, the negative electrode composite active material was mixed with carbon black Super-P, a carboxyl-containing binder CMC and SBR in a mass ratio of 96:1:1.3:1.7, added into solvent pure water and fully dissolved and stirred to obtain a negative electrode slurry, the negative electrode slurry was coated on a 6 μm thick copper foil, and the negative electrode sheet was obtained after drying, rolling and cutting.
[0091] (c) Preparation of lithium-ion batteries
[0092] The positive and negative electrode sheets prepared in (a) and (b) are assembled together with the separator, packaged and injected with electrolyte, and then the required lithium-ion batteries are obtained by chemical composition and charge and discharge tests are performed.
[0093] Comparative Example 3
[0094] A method for preparing a lithium ion battery comprises the following steps:
[0095] (a) Preparation of positive electrode for lithium-ion batteries
[0096] The ternary material is used as the positive electrode active material (the ternary material is consistent with that in comparative example 1), the positive electrode active material, the conductive agent Super-P, the carbon nanotube CNT slurry, and the binder PVDF are mixed in a mass ratio of 96.5:1:0.5:2, added into the solvent NMP through a multi-step method, and fully stirred to obtain the positive electrode mixed slurry, and then the positive electrode mixed slurry is coated on a 12 μm thick aluminum foil, and the positive electrode sheet is obtained after drying, rolling, and die-cutting.
[0097] (b) Preparation of lithium-ion battery negative electrode
[0098] The graphite negative electrode and the modified silicon oxide negative electrode were compounded in a mass ratio of 95:5 as a negative electrode composite active material, the negative electrode composite active material was mixed with carbon black Super-P, a carboxyl-containing binder CMC and SBR in a mass ratio of 96:1:1.3:1.7, added into solvent pure water and fully dissolved and stirred to obtain a negative electrode slurry, the negative electrode slurry was coated on a 6 μm thick copper foil, and the negative electrode sheet was obtained after drying, rolling and cutting.
[0099] (c) Preparation of lithium-ion batteries
[0100] The positive and negative electrode sheets prepared in (a) and (b) are assembled together with the separator, packaged and injected with electrolyte, and then the required lithium-ion batteries are obtained by chemical composition and charge and discharge tests are performed.
[0101] Comparative Example 4
[0102] A method for preparing a lithium ion battery comprises the following steps:
[0103] (a) Preparation of positive electrode for lithium-ion batteries
[0104] Prepare the lower layer spinel lithium manganate slurry, spinel lithium manganate particle size: D 50 : 13±1um, concentration: 60%, solvent is NMP.
[0105] Prepare the upper layer of lithium manganese iron phosphate slurry, lithium manganese iron phosphate particle size: D 50 : 1±0.5um, concentration: 50%, solvent is NMP.
[0106] The two types of positive electrode slurries were coated in multiple layers by extrusion coating, wherein the coating weight ratio of the lower layer to the upper layer was 3:7. The positive electrode sheets were obtained after drying, rolling and die-cutting.
[0107] (b) Preparation of lithium-ion battery negative electrode
[0108] The graphite negative electrode and the modified silicon oxide negative electrode were compounded in a mass ratio of 95:5 as a negative electrode composite active material, the negative electrode composite active material was mixed with carbon black Super-P, a carboxyl-containing binder CMC and SBR in a mass ratio of 96:1:1.3:1.7, added into solvent pure water and fully dissolved and stirred to obtain a negative electrode slurry, the negative electrode slurry was coated on a 6 μm thick copper foil, and the negative electrode sheet was obtained after drying, rolling and cutting.
[0109] (c) Preparation of lithium-ion batteries
[0110] The positive and negative electrode sheets prepared in (a) and (b) are assembled together with the separator, packaged and injected with electrolyte, and then the required lithium-ion batteries are obtained by chemical composition and charge and discharge tests are performed.
[0111] Comparative Example 5
[0112] A method for preparing a lithium ion battery comprises the following steps:
[0113] (a) Preparation of positive electrode for lithium-ion batteries
[0114] Prepare the lower layer polycrystalline ternary positive electrode material and nano manganese iron phosphate lithium positive electrode material in a mass ratio of 70:30 to prepare a mixed slurry; prepare the upper layer of manganese iron phosphate lithium slurry. Among them, the lower layer: polycrystalline ternary positive electrode material, the chemical formula is LiNi 0.8 Co 0.1 Mn0 .1 O2, particle size: 8-12 μm; nano-manganese iron lithium phosphate particle size: D 50 : 1±0.5μm, solvent type: NMP, concentration: 55%. Upper layer lithium manganese iron phosphate slurry: lithium manganese iron phosphate particle size: D 50 : 1±0.5μm, solvent type: NMP, concentration: 50%.
[0115] The two types of positive electrode slurries were coated in multiple layers by extrusion coating, wherein the coating weight ratio of the lower layer to the upper layer was 5:5, and the positive electrode sheets were obtained after drying, rolling and die-cutting.
[0116] (b) Preparation of lithium-ion battery negative electrode
[0117] The graphite negative electrode and the modified silicon oxide negative electrode were compounded in a mass ratio of 95:5 as a negative electrode composite active material, the negative electrode composite active material was mixed with carbon black Super-P, a carboxyl-containing binder CMC and SBR in a mass ratio of 96:1:1.3:1.7, added into solvent pure water and fully dissolved and stirred to obtain a negative electrode slurry, the negative electrode slurry was coated on a 6 μm thick copper foil, and the negative electrode sheet was obtained after drying, rolling and cutting.
[0118] (c) Preparation of lithium-ion batteries
[0119] The positive and negative electrode sheets prepared in (a) and (b) are assembled together with the separator, packaged and injected with electrolyte, and then the required lithium-ion batteries are obtained by chemical composition and charge and discharge tests are performed.
[0120] Lithium-ion battery safety testing:
[0121] Capacity test: The battery was charged and discharged at 0.33C and 1C respectively to obtain the battery capacity data at 0.33C and 1C.
[0122] Internal resistance test: Use a DC internal resistance tester to test the battery internal resistance.
[0123] Hot box test: Place the fully charged battery in an explosion-proof oven, start the test at 25°C and increase the temperature to 130°C at a rate of 5°C / min, maintain the temperature for 60 minutes, and record the temperature rise and voltage change of the battery.
[0124] Needle penetration test: At 25°C, use a 5mm steel needle to penetrate the geometric center of a fully charged battery at a speed of 25mm / s for 30 minutes, and record the temperature rise and voltage change of the battery.
[0125] Table 1. Battery internal resistance, battery capacity, and battery maximum temperature data when the hot box is 130°C
[0126]
[0127] By comparing the embodiment with comparative examples 1, 2, and 3, it can be seen that after being mixed with various positive electrode active materials and coated on the surface of the current collector, a multilayer positive electrode active material is coated on the current collector to form a positive electrode multilayer structure, the size of the intermediate layer positive electrode active material particles are compounded, the polycrystalline ternary positive electrode active material is composited with nano-lithium iron manganese phosphate, and the nano-lithium iron manganese phosphate particles are relatively fine, which can be filled in the gap between the ternary positive electrode active material and the lithium manganate positive electrode material, thereby improving the compaction density of the composite material and the contact between the particles, and reducing the internal resistance of the pole piece. The multilayer structure of the active material improves the battery rate charge and rate discharge capabilities, and the olivine structure lithium iron manganese phosphate material improves the battery safety performance.
[0128] From the comparison between Example 1 and Comparative Example 4 and Comparative Example 5, it can be seen that lithium manganese oxide can effectively improve the capacity ratio of the battery and reduce the internal resistance of the battery. However, due to the greater influence of lithium manganese iron phosphate on the internal resistance, although it can improve the safety performance of the battery, it will reduce the internal resistance and capacity ratio of the battery. In addition, it should be noted that the use of a large amount of lithium manganese iron phosphate in the upper layer will also lose the capacity and compaction density of the battery.
[0129] The lithium-ion batteries in the embodiments and comparative examples were tested for high and low temperature performance (1C constant current constant voltage charging to 3.65V, 1C discharge to 2.0V at different temperatures (25°C, 0°C), 1C discharge to 1.6V at different temperatures (-10°C, -20°C, -30°C)), and the results are shown in Table 2.
[0130] Table 2 High and low temperature performance test results
[0131] Group 25℃ 0℃ -10℃ -20℃ -30℃ Example 1 100% 98.8% 95.1% 89.7% 84.3% Example 2 100% 95.8% 92.3% 88.5% 81.9% Example 3 100% 92.4% 88.5% 85.2% 78.6% Comparative Example 1 100% 88.2% 81.9% 79.5% 67.1% Comparative Example 2 100% 82.3% 77.2% 73.2% 62.5% Comparative Example 3 100% 78.3% 74.2% 65.2% 57.5% Comparative Example 4 100% 89.1% 83.6% 80.4% 68.9% Comparative Example 5 100% 90.2% 85.8% 82.7% 71.1%
[0132] From the comparison between the examples and the comparative examples in Table 2, it can be seen that the low temperature resistance of the lithium battery is greatly improved by coating the positive electrode multilayer structure on the current collector.
[0133] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A lithium battery positive electrode sheet, characterized in that: A positive electrode multilayer structure including a current collector and attached to the current collector; The positive electrode multilayer structure is composed of a lithium iron manganese phosphate layer, a polycrystalline ternary material mixed lithium iron manganese phosphate layer and a lithium manganate layer from top to bottom, and the lithium manganate layer is attached to the surface of the current collector; The polycrystalline ternary material is lithium nickel cobalt manganese oxide.
2. The lithium battery positive electrode sheet according to claim 1, characterized in that: The current collector includes aluminum foil, copper foil and titanium mesh, preferably aluminum foil.
3. The lithium battery positive electrode sheet according to claim 1, characterized in that: The median particle size D50 of the lithium manganese iron phosphate is 200-1500nm, preferably 500-1200nm, and more preferably 800-1000nm; Preferably, the median particle size D50 of the polycrystalline ternary material is 6-12 μm, preferably 8-10 μm; Preferably, the median particle size D50 of the lithium manganate is 8-15 μm, preferably 10-13 μm.
4. The lithium battery positive electrode sheet according to claim 1, characterized in that: The chemical formula of the lithium nickel cobalt manganese oxide is LiNi x Co y Mn 1-x-y O2, where 0<x<1, 0<y<1, x+y<1; Preferably, the lithium manganese iron phosphate has an orthorhombic olivine crystal structure and a chemical formula of LiMn x Fe 1-x PO4, wherein 0.5≤x<1.0, preferably, 0.6≤x≤0.
8.
5. The lithium battery positive electrode sheet according to claim 1, characterized in that: The lithium manganate has a spinel structure.
6. The lithium battery positive electrode sheet according to claim 1, characterized in that: In the polycrystalline ternary material-blended nano-manganese iron lithium phosphate layer, the mass ratio of the polycrystalline ternary material to the manganese iron lithium phosphate is 50:50-99:2, preferably 70:30-80:
20.
7. The lithium battery positive electrode sheet according to claim 1, characterized in that: The coating weight ratio of the lithium iron manganese phosphate layer, the polycrystalline ternary material mixed lithium iron manganese phosphate layer and the lithium manganate layer is (1-10):(1-10):1, preferably (1-7):(2-8):
1.
8. A method for preparing a lithium battery positive electrode sheet according to any one of claims 1 to 7, characterized in that: The steps include: Prepare lithium iron manganese phosphate slurry; prepare polycrystalline ternary material mixed with lithium iron manganese phosphate slurry; prepare lithium manganate slurry; Lithium iron manganese phosphate slurry, polycrystalline ternary material mixed with lithium iron manganese phosphate slurry and lithium manganate slurry are sequentially coated on the surface of the current collector, and then dried, rolled and die-cut to obtain a lithium battery positive electrode sheet.
9. The preparation method according to claim 8, characterized in that: The coating is: applying multi-layer coating of the slurry by extrusion coating.
10. A lithium battery, characterized in that: The lithium battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte; the positive electrode sheet is the positive electrode sheet of the lithium battery according to any one of claims 1 to 7 or the positive electrode sheet of the lithium battery prepared by the preparation method according to claim 8 or 9.
Citation Information
Patent Citations
Negative electrode material for lithium battery and application of negative electrode material
CN117105231A
Lithium ion battery positive plate, preparation method thereof and lithium ion battery
CN113948673A
Lithium ion battery positive plate, preparation method and lithium ion battery
CN115621412A
Positive electrode active material, positive plate, preparation method of positive plate and lithium ion battery
CN116682951A
Positive electrode active material and positive electrode plate of lithium ion battery, and preparation method and application of positive electrode active material and positive electrode plate
CN116864677A
Cited By
Composite positive pole piece and lithium ion battery comprising same
CN120854481A
